Daya Cerna dan Karakteristik Fermentasi Rumen dengan Penambahan Asam Amino Terenkapsulasi secara In Vitro: In Vitro Digestibility and Rumen Fermentation Characteristics with the Addition of Encapsulated Amino Acid - Talapessy, Cornelia; Rahayuningsih, Mulyorini; Fidriyanto, Rusli; Fitri, Ainissya; Ridwan, Roni (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Amino acid protection is one of the efforts to improve livestock feed quality. Lysine is one of the limiting amino acids, which is easily degraded in the rumen, and thus requires a protection. This study aimed to determine the effect of protected lysine on cattle's digestive system and ruminal ecology in vitro. This study used encapsulation using xanthan gum and tannin (2% w/v) to protect lysine. The treatments consisted of P0 = unprotected amino acids; P1 = amino acids + 2 g xanthan gum; P2 = amino acids + 2 g tannin; P3 = amino acids + 2 g xanthan gum + 2 g tannin. Parameters observed included nutrient content, chemical activity, degradability of organic matter (OM) and crude protein (CP), and rumen fermentability (pH, N-NH3, VFA, gas kinetics, and CH4). A combination of xanthan gum and tannin coatings (P3) resulted in a higher effect (p<0.05) on rumen fermentation compared to others. The Undegraded DM and CP values in the rumen were 48% and 32%, respectively, and in the pepsin-HCl were 15% and 89%. All treatments did not change the rumen fermentability. In conclusion, protected amino acids has a effect on the cattle digestion system without disturbing the rumen ecology. Combining xanthan gum and tannin coatings provides the best results than using a single type of coating. Key words: amino acids, encapsulation, rumen fermentation, tannin, xanthan gum